Dealing with major depression in general practice - C.P. Freeman; J.A. Joska (South African Family Practice, 2012)
One in ten South Africans will be diagnosed with major depressive disorder (MDD) at some point in their lives. MDD is a potentially disabling condition that affects many spheres of an individual’s life and leads to marked social and occupational dysfunction. General practitioners are frequently required to diagnose and manage MDD, often in a time-pressured primary healthcare setting. This article aims to provide practitioners with an overview of MDD. It covers aspects of diagnosis, co-morbidity, pharmacology and special patient groups.